2023
DOI: 10.1126/sciadv.add5479
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Nfe2l1 increases proteasome activity and delays vision loss in a preclinical model of human blindness

Abstract: Proteasomes are the central proteolytic machines that are critical for breaking down most of the damaged and abnormal proteins in human cells. Although universally applicable drugs are not yet available, the stimulation of proteasomal activity is being analyzed as a proof-of-principle strategy to increase cellular resistance to a broad range of proteotoxic stressors. These approaches have included the stimulation of proteasomes through the overexpression of individual proteasome subunits, phosphorylation, or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
3
1
Order By: Relevance
“…Our findings necessitate reconsidering the role of the DDI2/Nrf1 pathway in basal and inhibitor-induced proteasome expression. Previous studies have also reported that DDI2/Nrf1 contributes to the maintenance of basal levels of proteasomes ( Chen et al, 2022 ; Siva et al, 2020 ; Waku et al, 2020 ) and that Nrf1 is essential for the basal proteasome expression in the brain ( Lee et al, 2011 ), liver ( Lee et al, 2013 ), and retina Wang et al, 2023 ; yet, in our experiments, the effects of DDI2 KO on the basal proteasome activity was not significant ( Figure 1—figure supplement 1 ). These differences may reflect that heavy secretory MM cells, embryonic cells, and certain specific tissues require higher levels of proteasome activity and use the DDI2/Nrf1 pathway to supplement other pathways responsible for proteasome expression ( Motosugi and Murata, 2019 ).…”
Section: Discussioncontrasting
confidence: 63%
“…Our findings necessitate reconsidering the role of the DDI2/Nrf1 pathway in basal and inhibitor-induced proteasome expression. Previous studies have also reported that DDI2/Nrf1 contributes to the maintenance of basal levels of proteasomes ( Chen et al, 2022 ; Siva et al, 2020 ; Waku et al, 2020 ) and that Nrf1 is essential for the basal proteasome expression in the brain ( Lee et al, 2011 ), liver ( Lee et al, 2013 ), and retina Wang et al, 2023 ; yet, in our experiments, the effects of DDI2 KO on the basal proteasome activity was not significant ( Figure 1—figure supplement 1 ). These differences may reflect that heavy secretory MM cells, embryonic cells, and certain specific tissues require higher levels of proteasome activity and use the DDI2/Nrf1 pathway to supplement other pathways responsible for proteasome expression ( Motosugi and Murata, 2019 ).…”
Section: Discussioncontrasting
confidence: 63%
“…The transcription factor Nrf1 mediates the increased expression of 26S proteasomes genes that occurs in response to proteasome inhibitors ( Sha & Goldberg, 2014 ). PSME4 , the gene that encodes PA200, also has a Nrf1 binding site close to its transcriptional start site ( Welk et al, 2016 ), and in mice in which Nrf1 was overexpressed, PSME4 transcription was increased in livers and retina, the only two tissues tested ( Wang et al, 2023 ). This, combined with previous data showing that proteasome subunits and PA200 are upregulated in contexts when the active form of Nrf1 is in the nucleus ( Sha & Goldberg, 2014 ; VerPlank et al, 2018 ), makes it very likely that Nrf1 mediates the upregulation of PSME4 when the proteasome is inhibited, and in S63del mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with systemic overexpression of Nrf1 exhibited increased proteasome synthesis. When crossed with a mouse model of human blindness, they showed a delayed age-related loss of photoreceptor neurons ( 39 ) .…”
Section: Proteasome Activation As a Promising Anti-aging Strategymentioning
confidence: 99%